The Impact of Repetitive Head Microtrauma on Cognitive Functions in Amateur Athletes – A Narrative Review - Strzalińska, Dominika; Piskor, Michał; Pazio, Klaudia; Chmielewski, Michał; Bajko, Julia; Kapusta, Kinga; Błażewicz, Juliusz; Bullmann, Agnieszka; Ciszewski, Artur; Kowalczuk, Maciej (Quality in Sport, 2026)
Repetitive head impacts (RHI) represent an important and often underestimated risk factor for impaired brain function in individuals participating in contact sports, including amateur athletes. Although they often do not result in clinically diagnosed concussions, research shows that even sub-concussive impacts can lead to measurable changes in brain structure and function, including alterations in white matter integrity and neural connectivity. Their cumulative nature plays a key role, as repeated low-intensity impacts may trigger processes such as axonal injury and neuroinflammation, which can develop gradually and remain undetected in standard clinical assessments. Neuroimaging studies have demonstrated subtle abnormalities even in asymptomatic individuals. These changes have been associated with declines in cognitive functions such as memory, attention, and processing speed, with their severity depending on exposure and individual susceptibility.